Arendt: totalitarismo e ideología (2021)
Around Hannah Arendt's book "The Origins of Totalitarianism" explanations are sought for the logic of the totalitarian State, that is, its way of operating and its consequences in the field of freedom, recognition and the way of life that indivuduals can expect in such a State. It is found that the terror that is imposed achieves a dehumanization of the individuals who, having lost everything rational, find themselves in the territory of the inconceivable.